Environmental project economics - Sholarin, E.; Awange, Joseph (2015)
© 2015, Springer International Publishing Switzerland. In this chapter, we strive to explain the application of microeconomic theory to environmental problems; limitations of market and government coordination of natural resource use, the relationship between the economy and the environment, and most especially, the cost-benefit analysis of green house gas effect, environmental pollution, and global warming.